ISSUES OF STATE SUPPORT FOR MODERNIZATION PROCESSES - Ermatov Ilhomjon Ismailovich (Academia Science Repository, 2023)
This article states that the overall modernization and development of the economy of the Republic of Uzbekistan requires an integrated approach to ensuring the security of the implementation of large infrastructure projects. It is stated that modernization is necessary not only in industry, but also in other areas, such as ensuring the safety of people's lives, preventing and eliminating the consequences of natural and man-made disasters, and preventing emergency situations.